2016
DOI: 10.3390/jcm5020018
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Involved in the Improvement of Lipotoxicity and Impaired Lipid Metabolism by Dietary α-Linolenic Acid Rich Salvia hispanica L (Salba) Seed in the Heart of Dyslipemic Insulin-Resistant Rats

Abstract: This study explores the mechanisms underlying the altered lipid metabolism in the heart of dyslipemic insulin-resistant (IR) rats fed a sucrose-rich diet (SRD) and investigates if chia seeds (rich in α-linolenic acid 18:3, n-3 ALA) improve/reverse cardiac lipotoxicity. Wistar rats received an SRD-diet for three months. Half of the animals continued with the SRD up to month 6. The other half was fed an SRD in which the fat source, corn oil (CO), was replaced by chia seeds from month 3 to 6 (SRD+chia). A referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 42 publications
5
48
0
7
Order By: Relevance
“…The compromised inflammatory state is usually attributed to higher levels of proinflammatory signaling from adipocytes. Dietary intervention studies have indicated that n-3 PUFA rich diet alleviates the metabolic syndromes through attenuating the inflammatory status of the system [23,24]. Hence, it was interesting to study the anti-inflammatory properties of Indian chia seeds in an in vitro setup.…”
Section: Resultsmentioning
confidence: 99%
“…The compromised inflammatory state is usually attributed to higher levels of proinflammatory signaling from adipocytes. Dietary intervention studies have indicated that n-3 PUFA rich diet alleviates the metabolic syndromes through attenuating the inflammatory status of the system [23,24]. Hence, it was interesting to study the anti-inflammatory properties of Indian chia seeds in an in vitro setup.…”
Section: Resultsmentioning
confidence: 99%
“…[13] Now with recent peer-reviewed evidence, chia seeds have been associated with possible effectiveness for allergies, angina, athletic performance enhancement, diabetes, cancer, coronary artery disease, myocardial infarctions, hormonal and endocrine disorders, hyperlipidemia, hypertension, stroke, vasodilatation, anticoagulant, and antiviral effects. [7,8,[13][14][15][16] Up until now, there have been no studies or analyses documenting adverse harms from chia seeds, specifically with obstruction as described above. [17][18][19] When added to liquid at room temperature (see Figure 3), dry chia seeds immediately begin to form a hydrogel gum capsule absorbing up to 27 times their weight in water, [6] which exhibits a non-Newtonian fluid behavior.…”
Section: Discussionmentioning
confidence: 99%
“…El contenido de glucose-6-fosfato, glucó-geno y la actividad de la enzima hexoquinasa se determinaron en homogeneizado de músculo cardíaco, como se describió previamente (11,12). Los niveles de glucosa-6-fosfato y glucógeno se expresan como µmol/gr de tejido húmedo.…”
Section: Determinación De La Presión Sanguíneaunclassified
“…Estudios previos de nuestro grupo y otros investigadores (12,24) constataron que la administración de una DRS induce un incremento de la presión arterial. Los resultados del presente trabajo señalan que un cambio en la fuente proteica (caseína por proteína de soja) fue capaz de normalizar la hipertensión.…”
Section: Actividad De La Enzima Hexoquinasa Contenido De Glucosa-6-funclassified
See 1 more Smart Citation